Productivity of Udayana University FISIP Lecturers: Bibliometric Analysis Using Lotka's Law - Kadek Dian Dwinanda Puspita; I Putu Suhartika; Richard Togaranta Ginting (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This study aims to determine the productivity of lecturers at the Faculty of Social and Political Sciences, Udayana University in a span of 10 years (2012–2021). The research method used is descriptive research with a quantitative approach. The results of this study proved that from 54 lecturers, 40 lecturers were found to have lecturer profile accounts on the Google Scholar website with a total publication of 940 journal articles. Lecturer productivity based on Lotka's Law gets an exponent value (n) 0.0050 with a value (C) 0.0350. This shows that the percentage of lecturers who contribute 2 articles to the lecturer profile on google scholar is on the observation results of 5%, while in the calculation of Lotka's theoretical value is 3.59%. After conducting the Kolmogorov-Smirnov Test, it was found that Dmax was greater than the critical value (0.8834 > 0.2150). Based on these results, it was found that there was a significant difference between the theoretical value of Lotka Law and the results of observations in journals indexed by google scholar in the FISIP lecturer profile for 2012–2021.